Influence of T cation on the vibrational properties of ferroelectric Ca2TO4 (T = Si, Ti, Mn, Ge) compounds - Neenu Saini; Ruby Jindal; Archana Tripathi; Harleen Kaur; Raminder Kaur (Chemical Physics Impact)
The analysis of Raman and Infrared (IR) phonons in monolayered tetragonal Ca2TO4 (T = Si, Ti, Mn, Ge) compounds, which exhibit D174h symmetry and belong to the I4/mmm phase of space group 139 with Z = 2, has been conducted using normal coordinates. The Ca2TO4 (T = Si, Ti, Mn, Ge) compounds are the first members of the Ruddlesden-Popper (RP) series denoted as Can+1TO3n+1 (T = Si, Ti, Mn, Ge) with n = 1. Nine Short-Range Force Constants (SRFC) have been included in theoretical calculations to analyze the optical phonons of Ca2TO4 (T = Si, Ti, Mn, Ge) compounds within the I4/mmm phase. The assignments of optical vibrational modes in Ca2TO4 (T = Si, Ti, Mn, Ge) compounds have been determined using Wilson's GF-Matrix Method and cross-referenced with data obtained from similar structural characteristics. The analysis also involved studying how the exchange of cation-T (T = Si, Ti, Mn, Ge) impacts the lattice dynamics of the isostructural compounds Ca2TO4 (T = Si, Ti, Mn, Ge) in the context of monolayered tetragonal structures. In this analysis, a comparison has been made between the vibrational modes at the Zone Center, the force constants, and bond lengths to assess the influence of the cation exchange. The frequencies predominantly influenced by the T-atoms (T = Si, Ti, Mn, Ge) exhibit distinctive characteristics that vary with atomic number, underscoring the profound impact of T-atoms (T = Si, Ti, Mn, Ge) size on vibrational properties of Ca2TO4 (T = Si, Ti, Mn, Ge) compounds. The analysis of force constant variations between Ca2TO4 (T = Si, Ge) and Ca2TO4 (T = Ti, Mn) revealed differences attributed to the distinctive orbital setups of the T-atoms. Furthermore, for each normal mode in the Ruddlesden-Popper phase Ca2TO4 (T = Si, Ti, Mn, Ge), the examination of Potential Energy Distribution (PED) sheds light on the significant impact exerted by Short-Range Force Constants on the calculated vibrational modes, providing a deeper understanding of their behavior and interactions.